Associations between food insecurity and psychotropic medication use among women living with HIV in the United States. (2020) - Whittle, Henry J.; Wolfe, William R.; Sheira, Lila A.; Frongillo, Edward A.; Palar, Kartika; Merenstein, Daniel; Wilson, Tracey E.; Adedimeji, Adebola; Cohen, Mardge H.; Wentz, Eryka L.; Tien, Phyllis C.; Weiser, Sheri D.
Abstract: Aims: Psychotropic prescription rates continue to increase in the United States (USA). Few studies have investigated whether social-structural factors may play a role in psychotropic medication use independent of mental illness. Food insecurity is prevalent among people living with HIV in the USA and has been associated with poor mental health. We investigated whether food insecurity was associated with psychotropic medication use independent of the symptoms of depression and anxiety among women living with HIV in the USA. Methods: We used cross-sectional data from the Women's Interagency HIV Study (WIHS), a nationwide cohort study. Food security (FS) was the primary explanatory variable, measured using the Household Food Security Survey Module. First, we used multivariable linear regressions to test whether FS was associated with symptoms of depression (Center for Epidemiologic Studies Depression [CESD] score), generalised anxiety disorder (GAD-7 score) and mental health-related quality of life (MOS-HIV Mental Health Summary score; MHS). Next, we examined associations of FS with the use of any psychotropic medications, including antidepressants, sedatives and antipsychotics, using multivariable logistic regressions adjusting for age, race/ethnicity, income, education and alcohol and substance use. In separate models, we additionally adjusted for symptoms of depression (CESD score) and anxiety (GAD-7 score). Results: Of the 905 women in the sample, two-thirds were African-American. Lower FS (i.e. worse food insecurity) was associated with greater symptoms of depression and anxiety in a dose–response relationship. For the psychotropic medication outcomes, marginal and low FS were associated with 2.06 ( p < 0.001; 95% confidence interval [CI] = 1.36–3.13) and 1.99 ( p < 0.01; 95% CI = 1.26–3.15) times higher odds of any psychotropic medication use, respectively, before adjusting for depression and anxiety. The association of very low FS with any psychotropic medication use was not statistically significant. A similar pattern was found for antidepressant and sedative use. After additionally adjusting for CESD and GAD-7 scores, marginal FS remained associated with 1.93 ( p < 0.05; 95% CI = 1.16–3.19) times higher odds of any psychotropic medication use. Very low FS, conversely, was significantly associated with lower odds of antidepressant use (adjusted odds ratio = 0.42; p < 0.05; 95% CI = 0.19–0.96). Conclusions: Marginal FS was associated with higher odds of using psychotropic medications independent of depression and anxiety, while very low FS was associated with lower odds. These complex findings may indicate that people experiencing very low FS face barriers to accessing mental health services, while those experiencing marginal FS who do access services are more likely to be prescribed psychotropic medications for distress arising from social and structural factors.